The Role of Philosophy of Science in Social Studies Learning Activities using the Think Talk Write (TTW) Cooperative Learning Model - Nova Amelia Putri; Siti Fatimah; Syafri Anwar (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2026)
This article aims to reflect on the relevance of the role of philosophy of science in social studies learning activities using the Think Talk Write cooperative learning method. This study uses a qualitative method with a descriptive-philosophical approach, a type of library research Primary data was taken from various major philosophical works discussing the theme of philosophy of science and its application in education, while secondary data included various additional literature, such as scientific articles, social studies learning theory books, previous research on the TTW model, and other academic publications that offer empirical and pedagogical contexts on the application of philosophy of science in education. The conclusion is that the philosophy of science in learning activities using the Think Talk Write model plays a very important role in encouraging activities in social studies learning through the process of thinking, speaking and then writing about the learning process being carried out.